(untitled) (Ius Novum, 2020)
The article presents an analysis of legal solutions that are in force in England, Wales, Scotland, Northern Ireland and the Republic of Ireland concerning an offence of self-liberation (escape) from lawful custody, an offence of unlawfully being at large after the conditional release expired or was recalled and an offence of facilitating escape from lawful custody, liberating or allowing a person to escape. The article aims to present the regulations and compare them with each other and the solutions adopted in the Polish Criminal Code. The research conducted made it possible to establish many similarities between regulations that are in force in the British Isles and between them and Articles 242 and 243 of the Polish Criminal Code.